The Role of Urban Green Spaces in Enhancing Environmental Health - Aqirah, Nurul; Salsabila, Nadya; Indriyani, Nur (Journal of Asian-african Focus in Health, 2025)
Urban green spaces and their components of parks, gardens and forests stand essential to environmental health by delivering multiple advantages which support both ecological and social health and public welfare. The review analyzes the major environmental health benefits of urban green spaces which primarily originate from their regulatory functions for air quality, their climate control capabilities and their service capacity to biodiversity preservation. The presence of green spaces in urban areas enhances air quality since they capture pollutants like carbon dioxide together with nitrogen dioxide and particulate matter thus diminishing respiratory disease risks. The green spaces serve as heat island regulators that create cooling effects which become particularly crucial during periods of extensive heat. Ecosystem balance in urban areas benefits from urban green spaces through their provision of habitats for plant and animal species allowing the enhancement of biodiversity. The designed areas enhance climate regulation through their capability to capture carbon while performing effective stormwater management and building urban climates that resist climate change impacts. The review demonstrates why urban planners should prioritize adding green infrastructure because it deals with neighborhood environmental concerns at the same time as solving worldwide problems including climate change and biodiversity reduction. Cities develop sustainable healthier living environments when designers focus on green spaces correctly and set their priorities.